(3GdaJM GdfHhi aj GdehdO GdehShis - (3eMeO GdJGadGJjs
(3ChdgG (B:s
(3GdMeO ddg GdPi CfRd GdJhQGI Ydi QShdg GdcQje s
(3BNQgG (B:s
,(3gHJ GdQMeGJ Ydi bQGA ehdOg hehdO SjO GdBfGe Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYTQhfs
(3GdebUhO Hg ehdO ehSi Ydjg GdSdGes
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ ESMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs